Identifikasi risiko keselamatan dan kesehatan kerja untuk mempertahankan zero accident - Lestari, Nina Puji; Dewantari, Nustin Merdiana; Umyati, Ani (Universitas Sultan Ageng Tirtayasa, 2022)
Occupational safety and health (OSH) are essential factors in supporting the smooth production process in a company. Z company received a zero-accident award for 2016 until 2022 because it implements OSH appropriately. This study aims to determine the potential hazard, determine the value of the risk level, and determine risk control in the repair work of the production building. The method used is HIRARC (Hazard Identification Risk Assessment and Risk Control). The results are obtained from 23 potential risks from 3 activities in the repair of production buildings. The level of risk in building repair activities tends to be low and moderate. Risk control recommendations for the three jobs are elimination, administrative, engineering, and PPE use.